Delamination of sub-crustal lithosphere beneath the Isthmus of Tehuantepec, Mexico: Insights from numeric modelling. (September 2019) - Manea, M.; Manea, Vlad C.; Ferrari, L.; Orozco-Esquivel, T.
Abstract: The Isthmus of Tehuantepec (IT) is a tectonically active and complex physiographic province in southern Mexico marked by an anomalous volcanism with unusual location and geochemical signature, an extensional stress regime and a well-imaged high seismic-velocity anomaly in form of a slab-like structure whose origin remains still not well understood. Here we use numeric modelling, tectonic information and composition of volcanic rocks from the Los Tuxtlas Volcanic Field (LTVF) to reconstruct the geodynamic evolution of the Isthmus of Tehuantepec from the Late Miocene to the present, and propose a model that reconciles the seismic observations with the tectonic evolution of the region. Using a high-resolution thermomechanical petrological coupled model, we show that rollback of delaminated continental lithosphere and associated asthenospheric upwelling provides a plausible mechanism for generating the observed high seismic-velocity anomalies beneath the Isthmus of Tehuantepec. Our model proposes that delamination of the entire lithospheric mantle initiated some 7 Myr ago by infiltration of hot and buoyant asthenospheric material into the base of the crust, when a slab gap appeared in the subducting Cocos slab. A geodynamic model involving sub-crustal lithosphere delamination reconciles the geological and geophysical observations and explains the complex oceanic-continental tectonics of the Isthmus of Tehuantepec.